2017
DOI: 10.1111/jmft.12233
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Experiences of Marriage Preparation Among U.S. Muslims: Multiple Voices from the Community

Abstract: Although Muslims in the United States are a growing population, there is limited research on their relational patterns and how they prepare for marriage. We conducted in-depth interviews with 32 members of the Muslim community in Southeast Michigan including married individuals, divorced individuals, therapists, and imams (Muslim religious leaders) to explore their perceptions and experiences of marriage preparation. Our analysis revealed that marriage preparation varies but is less likely to involve a require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
1
11
0
10
Order By: Relevance
“…This is not true for Moroccan men and women, in whom the maintenance of other institutions and social relations, such as family or religious practice, displaces the importance placed on couple relationships. The decreased amount of time and importance that Muslim women place on love and couplehood coincides with other studies that assert that couple relationships for Muslim women are based more on a socio-economic materiality than on intangible sentimentality (Killawi et al, 2018). Morini (2016) explains that for Moroccan women who immigrated to Italy, love does not occupy the central space in their lives that is socially attributed to them; instead, they establish strong affective bonds and ties with other women, far from the stereotype of the submissive woman on her knees.…”
Section: Relational Structure Of Spanish and Moroccan Couplessupporting
confidence: 81%
See 1 more Smart Citation
“…This is not true for Moroccan men and women, in whom the maintenance of other institutions and social relations, such as family or religious practice, displaces the importance placed on couple relationships. The decreased amount of time and importance that Muslim women place on love and couplehood coincides with other studies that assert that couple relationships for Muslim women are based more on a socio-economic materiality than on intangible sentimentality (Killawi et al, 2018). Morini (2016) explains that for Moroccan women who immigrated to Italy, love does not occupy the central space in their lives that is socially attributed to them; instead, they establish strong affective bonds and ties with other women, far from the stereotype of the submissive woman on her knees.…”
Section: Relational Structure Of Spanish and Moroccan Couplessupporting
confidence: 81%
“…According to the data obtained, the family continues to be the primary space for affective learning for all the groups, and is recognised as the primary space for acquiring and forming affective and relational patterns (Morris, Silk, Steinberg, Myers, & Robinson, 2007). Familism is a characteristic of collectivist societies such as Morocco (Dammacco, 2005), where, despite migration, families maintain a very active role in the courtship process and marriage in the first and second Muslim generations (Killawi et al, 2018). Familism is also characteristic of Spain, which has been identified as the most family-centred country in the European Union.…”
Section: Diversity In the Factors Involved In The Sociocultural Construction Of Lovementioning
confidence: 99%
“…An individualistic culture is a culture in which people view themselves as unique and separate entities, a culture that focuses on oneself. The collectivist culture is a culture in which people tend to think about themselves concerning others, a culture that focuses on others (22). The findings of Fernandez et al (23) showed that individuals in these communities stress the loyalty to the ascribed groups and responsibilities towards families.…”
Section: Discussionmentioning
confidence: 99%
“…Although empirical studies indicate ME programmes to be successful at teaching couples the skills needed to create and sustain healthy relationships (Schmidt et al, 2016;Jacobi, 2017;Quirk et al, 2014;Worthington, Berry, Hook, Davis, Scherer, Griffin, Wade, Yarhouse, Ripley, Miller, Sharp, Canter & Campana, 2015;Markman & Rhoades, 2012), there are limitations. The literature often reports empirical studies regarding marriages and ME relationship interventions to be predominately conducted in Western countries with a specific focus on White populations (O'Halloran, Rizzolo, Cohen & Wacker, 2013;Killawi, Fathi, Dadras, Daneshpour, Elmi & Altalib, 2018;Su, Miller, Canlas, Hsiao & Willoughby, 2015;Muro, Holliman & Luquet, 2016b). Hence there is limited data on their effectiveness in other populations such as in SA.…”
Section: The Development Of a Culturally-appropriate Marriage Enrichment Programme For Black African Married Couples: Overview Of Programmentioning
confidence: 99%
“…'Marriage preparation' entails couples being educated and equipped before getting married to prevent and deal with potential challenges experienced in the relationship (Olson, Olson & Larson. 2012;Killawi et al, 2018;Haselau, Kasiram & Simpson, 2015;Duncan, Rogers & McAllister, 2017). 'Marriage guidance' entails help provided in this instance to couples in order to encourage self-awareness, independence, making choices and adequate response to life challenges (Ansah-Hughes & Practice, 2015).…”
Section: The Nature Of Marriage Enrichment and Backgroundmentioning
confidence: 99%